Portfolio Management Challenges of Global Private Equity Firms Operating in the UK and the Emerging Economies: China and India - Sorby, Debora (2008)
In the early 1990s, the emphasis on driving value from UK private equity investments was very much focused on deal making. Many UK private equity firms merely monitored their portfolio and adopted the hands-off approach to their investees. The UK private equity market has matured over the past decade meaning increased competition, access to increasingly more investment funding and awareness of the availability of private equity. This has meant that in order to generate the returns private equity firms have historically been used to they have had to consider how value can be added across the whole lifecycle of the investment. They have had to supplement their acknowledged deal skills and become more actively involved in their investee companies by using the hands-on approach to portfolio management. Also because the UK private equity market is considered a mature market , some of the larger, well established private equity firms started looking at other markets outside the UK, in particular the emerging economies of China and India to generate the returns they were used to. This study addresses the reasons why private equity firms have decided to expand into China and India. It explores how deals are sourced, investments, divestments and how the portfolio is managed given the challenges faced in each country. For an in-depth view of how a private equity firm evolved from being a UK centric firm, very much focusing on deals and a hands-off approach to their investee companies and then how it emerged into the business it is today, this project uses 3i plc as a case study. 3i plc illustrates clearly how changing the portfolio management approach takes time but the change in approach was vital if they were to become the global player they are today.